2019
DOI: 10.1080/22221751.2019.1595984
|View full text |Cite
|
Sign up to set email alerts
|

The role of ArlRS in regulating oxacillin susceptibility in methicillin-resistant Staphylococcus aureus indicates it is a potential target for antimicrobial resistance breakers

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA), also known as oxacillin-resistant S. aureus, is a leading cause of community and hospital associated infections globally. In this work, we found that deletion of the arlRS two-component system genes in the USA300 and USA500 strains resulted in increased susceptibilities to oxacillin (8–16-fold decrease in minimal inhibitory concentrations). In USA300Δ arlRS, transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 60 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…It was recently shown that ArlRS activates expression of the transcriptional regulator spx (Bai et al , ). Spx interacts directly with RNA polymerase and is involved in the disulfide stress response in Firmicutes (Hillion and Antelmann, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently shown that ArlRS activates expression of the transcriptional regulator spx (Bai et al , ). Spx interacts directly with RNA polymerase and is involved in the disulfide stress response in Firmicutes (Hillion and Antelmann, ).…”
Section: Resultsmentioning
confidence: 99%
“…). The ArlRS TCS was also recently shown to directly regulate spx expression (Bai et al , ). We show that this regulation occurs at the spx P2 promoter, which contains a similar ArlR‐binding site (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations